Mural unicystic ameloblastoma with multifarious histopathological patterns: An exquisite case report - Sahanaz Praveen Ahmed; Nandhini Gunasekaran; Preethi Arunachalam; Ramesh Kumar Annasamy (Wolters Kluwer Medknow Publications, 2020)
Ameloblastoma is a true benign neoplasm of odontogenic epithelial origin mostly seen in the mandible. After odontoma, it is the second most commonly seen odontogenic neoplasm. Ameloblastoma comprises of several clinical, radiological and histological varieties, making it the most significant odontogenic neoplasm. Among these, the unicystic type is the least explored due to the fewer numbers of reported cases. Clinically and radiographically, it represents a cyst, but displays classic ameloblastomatous epithelial lining part of the cyst cavity, with or without intraluminal and/or mural tumor growth. We present an unusual case of unicystic ameloblastoma showing mural proliferation with mixed histological pattern [Plexiform, Follicular and Acanthomatous] of the mandible in a 32-year-old male.